Malaysian Integrated Population Program Performance: Its Relation to Organizational and Integration Factors - Fong, C. O. (Management Science, 1985)
The aim of this paper is two-fold. Firstly, it seeks to compare the efficacy of the Malaysian integrated population (i.e., integration of family planning with health) program with its categorial family planning counterpart. Secondly, it attempts to identify the organizational factors and the ‘integration’ factors (operationalized as staff integrative linkages) that result in better program performance for the two programs. On the basis of effectiveness of family planning diffusion, the results of the analysis indicate that the Malaysian integrated population program is more effective than its categorial counterpart. Further, integrative linkage variables were found to be an important group of variables that results in the improved effectiveness of the integrated program. This suggests that future expansion of the Malaysian population program (and population programs of other developing countries in a similar stage of development as Malaysia) should be through the approach of integrating family planning services with the health network, rather than through the expansion of the categorial family planning organization.